2009
DOI: 10.1002/jts.20428
|View full text |Cite
|
Sign up to set email alerts
|

Participant reactions to a pretreatment research assessment during a treatment outcome study for PTSD

Abstract: Participants' reactions to pretreatment assessments have not been studied as part of a randomized clinical trial (RCT) for posttraumatic stress disorder (PTSD). The current study examined participants' reactions in women with PTSD who completed pretreatment assessments during an RCT. We assessed participant reactions (N = 100) to a pretreatment assessment that included selfreport questionnaires, interviews, and psychophysiological assessment. Results indicated that participation in pretreatment assessment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Somewhat more recently, Resick and colleagues [9] assessed evaluations of the pre-treatment assessments among female survivors of childhood and/or adult interpersonal violence with PTSD (N = 100) who were seeking psychotherapy (3 days of assessment (3–4 h/d.). Findings showed that a small group evaluated the questionnaires as (very) distressing (8%) compared to the clinical interview (19%) and talking about the trauma (53%).…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat more recently, Resick and colleagues [9] assessed evaluations of the pre-treatment assessments among female survivors of childhood and/or adult interpersonal violence with PTSD (N = 100) who were seeking psychotherapy (3 days of assessment (3–4 h/d.). Findings showed that a small group evaluated the questionnaires as (very) distressing (8%) compared to the clinical interview (19%) and talking about the trauma (53%).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a nonclinical sample of college students, Cromer and colleagues (2006) found that participants did not perceive greater distress from trauma-related questions than from other personal questions about topics such as weight and academic achievement. Participants with PTSD rated questionnaires about trauma as less stressful, and diagnostic interviews more stressful, than a psychophysiological task with trauma-unrelated stressors (Resick et al, 2009). One the other hand, participants with PTSD also report greater distress after completing trauma-related vs. unrelated questionnaires (Ferrier-Auerbach et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined distress (e.g., dislike of study procedures or regret about participation) and perceived benefits directly related to participation (Walker, 1997; Parslow et al, 2000; Cromer et al, 2006; Deprince and Chu, 2008; Resick et al, 2009) but have not examined participants’ potential for harm to self or others. In their study, Cromer et al (2006) found that undergraduates rated trauma-related questionnaires no more distressing, compared to everyday events, than other questionnaires about academic achievement, body image, parents’ income, race, and sexuality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of empirical studies have measured PTSD status in participants and subsequently evaluated participants' reaction to their research participation (e.g., Carlson et al 2003;Edwards et al 2009;Parslow et al 2000;Resick, Iverson, and Artz 2009;Weitlauf et al 2007). Uniformly, such studies have reported that a majority of participants with PTSD report minimal distress in response to questions about their traumatic experiences or about their PTSD symptoms, and findings are robust across diverse measures of reactions to research participation and study modalities (e.g., mailed surveys, psychophysiological evaluation of distress, and interviews that included direct inquiry about prior trauma exposure; Griffin et al 2003;Walker et al 1997).…”
Section: Beneficence and Nonmaleficencementioning
confidence: 99%